Opportunities and Challenges for Ecotourism Development at Pyara Lake in Kanchanpur District of Western Nepal - Ghimire, Samrat; Khatiwada , Shreekanta S; Rawal, Krishna; Joshi , Deepak Raj (Dhaulagiri Journal of Contemporary Issues, 2025)
Tourism at Pyara Lake, located in the Kanchanpur District of Western Nepal, holds significant potential for sustainable development, as revealed by a comprehensive SWOT analysis. This study assesses the opportunities and challenges of ecotourism development in the Pyara Lake area. Primary data were collected through semi-structured questionnaires and interviews with residents involved in lake conservation activities, supplemented by field observations. A mixed-methods research design, incorporating both qualitative and quantitative approaches, was employed to analyze the data The lake’s natural beauty, biodiversity, and cultural significance make it an attractive destination for diverse tourists. Most visitors are students, who prefer affordable transportation like bikes and auto-rickshaws. Sightseeing and boating are the primary activities, highlighting the water-based nature tourism. The tourism contributes notably to local livelihoods, with major employment in hospitality. Despite the limited infrastructure investment, significant increase in local income levels from post-tourism demonstrates the sector’s economic impact. Challenges such as poor accessibility, inadequate facilities and environmental degradation must be addressed through strategic community involvement. Opportunities for promoting eco-tourism, cultural heritage, and sustainable practices present pathways to attract ecotourism and ensure equitable economic benefits. By investing in infrastructure, enhancing local engagement, and leveraging its natural and cultural assets, Pyara Lake can emerge as a model for sustainable tourism. Strategic collaboration among stakeholders will be essential to overcoming challenges and ensuring tourism sustainability.